Analisis pola konsumsi rumah tangga studi kasus rumah tangga industri kerajinan kaleng di desa babakan Kabupaten Lombok Barat tahun 1992 = The Analysis of Household Consumption Pattern A Case Study The Households of ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
The purposes of the investigation were (1) to show a description on the consumption patterns of the can industry households in the Babakan Village of the West Lombok Regency in 1992